THE EFFECT OF CAR, FDR, NPF, GEARING RATIO AND CORPORATE GOVERNANCE ON PROFITABILITY OF SHARIA BANK - Suteja, Ghamal Irwana; Majidah, Majidah (Jurnal Ekonomi Balance, 2020)
Sharia Commercial Bank has quite good growth in Indonesia as the country with the largest Muslim population in the World and it's time to be a pioneer in the development of the sharia industry. Therefore it is necessary to increase bank performance in accordance with sharia principles. Bank performance can be measured using profitability ratios which are proxied using Return on Assets (ROA). The purpose of this study is to determine the profitability of Islamic banks and the factors that influence it. The population in this study is Sharia Commercial Banks in Indonesia. The samples produced were 60 samples using purposive sampling. Data in this study were analyzed with descriptive statistics and panel data regression. The results showed that CAR, FDR, NPF, gearing ratio and corporate governance had a simultaneous effect on profitability. Partially, CAR and NPF affect profitability. Although the results of the study state that gearing ratios and corporate governance do not affect profitability, gearing ratios and corporate governance are the renewal variables in this study.